2016
DOI: 10.3389/fpls.2016.01901
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Nitrogen and Carbon Is Regulated by Nodulation and Mycorrhizal Networks in Soybean/Maize Intercropping System

Abstract: Soybean/maize intercropping has remarkable advantages in increasing crop yield and nitrogen (N) efficiency. However, little is known about the contributions of rhizobia or arbuscular mycorrhizal fungi (AMF) to yield increases and N acquisition in the intercropping system. Plus, the mechanisms controlling carbon (C) and N allocation in intercropping systems remain unsettled. In the present study, a greenhouse experiment combined with 15N and 13C labeling was conducted using various inoculation and nutrient trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 38 publications
(62 reference statements)
2
28
2
Order By: Relevance
“…Our results thus demonstrate a very balanced investment of the two plants into the CMN and that this investment is not substantially affected by elevated temperature. Our data are thus in direct contrast to previous research showing that one or the other plant dominates the C supply to the CMN ( Walder et al, 2012 ; Wang et al, 2016 ). The previous experiments had all used phylogenetically more distant plant species pairs, and it has been shown that plant size and/or presence of rhizobia could affect the C inputs into the CMN ( Nakano et al, 1999 ; Wang et al, 2016 ; Weremijewicz et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results thus demonstrate a very balanced investment of the two plants into the CMN and that this investment is not substantially affected by elevated temperature. Our data are thus in direct contrast to previous research showing that one or the other plant dominates the C supply to the CMN ( Walder et al, 2012 ; Wang et al, 2016 ). The previous experiments had all used phylogenetically more distant plant species pairs, and it has been shown that plant size and/or presence of rhizobia could affect the C inputs into the CMN ( Nakano et al, 1999 ; Wang et al, 2016 ; Weremijewicz et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our data are thus in direct contrast to previous research showing that one or the other plant dominates the C supply to the CMN ( Walder et al, 2012 ; Wang et al, 2016 ). The previous experiments had all used phylogenetically more distant plant species pairs, and it has been shown that plant size and/or presence of rhizobia could affect the C inputs into the CMN ( Nakano et al, 1999 ; Wang et al, 2016 ; Weremijewicz et al, 2016 ). Because we used plant species closely related phylogenetically and of similar size and growth rates (although not necessarily so under all temperatures), such asymmetry in C feeding of the CMN as seen in previous experiments may not have developed in our case.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With 14 C labeling in rice leaves, both enhanced 14 C activity in watermelon (Citrullus lanatus) leaves and increased P uptake and translocation in rice were shown, thus AM fungus mediated the C and P trade between intercrops (Ren et al, 2013). In a growth chamber 13 CO 2 -labeling experiment, inoculation with AM fungi increased 13 C content in maize shoots and decreased 13 C content in soybean roots, indicating that maize invested less C than soybean into the CMNs (Wang et al, 2016). Walnut (Juglans nigra) tree showed higher ∂ 13 C ( 13 C/ 12 C ratio) in leaves but lower ∂ 13 C in root adjacent mycelium compared to the neighboring maize, suggesting the potential C transfer from walnut to maize via the CMNs (van Tuinen et al, 2020).…”
Section: The Mediation Of Resource Transfer and Facilitation Between Intercrops Via Cmnsmentioning
confidence: 96%
“…The maize/legumes intercropping systems enriched the soil biodiversity and spores of AMF in the root-zone soil (Punyalue et al, 2018). Intercropping facilitated nitrogen transfer from soybeans to maize on co-inoculation with AMF, as shown by 15 N labeling (Wang et al, 2016). AMF application in dill/common bean intercropping systems can enhance the Fe, zinc (Zn), and manganese (Mn) contents of dill and its competitive ability against weeds (Weisany et al, 2016a,b).…”
Section: Effect Of Rhizosphere Change On Iron Acquisition In Leguminomentioning
confidence: 99%